STUDI INTERPRETATIF IMPLIKASI SPIRITUALITAS TERHADAP KUALITAS LAYANAN PENGEMUDI GRAB SURABAYA - Sugiharto Gunawan (Prosiding Seminar Nasional Sinergitas Multidisiplin Ilmu Pengetahuan dan Teknologi, 2019)
This study aims to determine the implications of spirituality on the quality of Grab Surabaya driver services. The research paradigm used is qualitative research. The subjects in this study were representatives of GrabTaxi driver partners and representatives of GrabTaxi passengers. The technique of determining the sources in this study was using purposive sampling. The method of data collection conducts field studies through interviews. The data analysis technique used in this study is qualitative data analysis. This study also uses the data validity test in the form of triangulation. The results of this study indicate that Grabcar drivers who have high spirituality will tend to have good ethics at work and not too much pursuit of bonuses in determining the length of their work. Grabcar drivers who have chosen jobs according to their passion will tend to be able to feel pleasure in carrying out the work. The reason and main motivation of the drivers preferring to be the driver of Grabcar is first, the economic factor to meet their needs and their families, besides being a driver of Grabcar, it is known that it also provides great benefits, especially in terms of the economy. Grabcar users' satisfaction with the quality of online taxi services in the city of Surabaya lies in the comfort, accuracy and safety of the passengers of the Grabcar itself.